2011
DOI: 10.1371/journal.pone.0018778
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Specific Effect Associated with Conditional Transgene Expression Based on Cre-loxP Strategy in Mice

Abstract: Transgenes flanked by loxP sites have been widely used to generate transgenic mice where the transgene expression can be controlled spatially and temporally by Cre recombinase. Data from this approach has led to important conclusions in cancer, neurodevelopment and neurodegeneration. Using this approach to conditionally express micro RNAs (miRNAs) in mice, we found that Cre-mediated recombination in neural progenitor cells caused microcephaly in five of our ten independent transgenic lines. This effect was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…S1B), which led to aberrant chromosome segregation (SI Appendix, Fig. S1C) and death of proliferating cells during brain development (45). Because of this artifact, we were precluded from inducing the transgene expression selectively in the CNS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1B), which led to aberrant chromosome segregation (SI Appendix, Fig. S1C) and death of proliferating cells during brain development (45). Because of this artifact, we were precluded from inducing the transgene expression selectively in the CNS.…”
Section: Resultsmentioning
confidence: 99%
“…As a control, we also generated a line of Tg mice that constitutively expressed a scrambled amiRNA (amiR-SCR) using the same construct design and the same strategy to convert from the GFP-expressing parent line to the constitutive RFP-expressing and amiR-SCR-expressing line (45). Western blot analysis revealed that these Tg mice expressed a higher level of transgene than the amiR-TDP43 mice in the CNS (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These animal models demonstrate that mutant SOD1 expression within non-neuronal cells can be a determinant of disease progression, while the mutant enzyme’s presence in motor neurons contributes to disease onset. However, a recent study showed that such models utilizing conditional transgene expression based on a Cre-loxP strategy was associated with microencephaly, which may cause the loss of SOD1-expressing cells during development leading to observed phenotype (Qiu et al , 2011)…”
Section: Peroxynitrite Promotes Toxic Glial Phenotypesmentioning
confidence: 99%
“…The approach was applied for CNS knockdown (37). But it did not work due to unintended effects from inverted tandem integrations.…”
Section: Discussionmentioning
confidence: 99%